Analisis Pengaruh CAR, NPL, LDR, NIM, dan BOPO Terhadap Profitabilitas Bank (Perbandingan Bank Umum Go Public Dan Bank Umum Non Go Public Di Indonesia Periode Tahun 2011-2014) - Avrita, Risky Diba; Demi Pangestuti, Irene Rini (Diponegoro Journal of Management, 2016)
This study aimed to analyze the influence of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), Operating Expenses to Operating Income (BOPO) of the Banking Profitability (ROA). The population in this study is the object of all commercial banks in Indonesia which consists of banks go public and non go public banks listed in the Otoritas Jasa Keuangan in 2014. While the number of samples used by 69 commercial banks, comprised of 23 banks go public and 46 bank non go public. Samples were taken by purposive sampling system with the criterion that the banking companies whose financial statements have been published by the Otoritas Jasa Keuangan in the period 2011-2014. The method used in this study using multiple regression analysis with the hypothesis test tools t test and F test. Through the simultaneous hypothesis test (test F) note that the CAR, NPL, LDR, NIM and ROA have significant effect on the profitability of banks, both banks go public and non bank go public with a significance level of 0.000. While based on the partial hypothesis test (t test) on commercial banks to go public indicates that the variable NPL, NIM and BOPO significant effect on bank profitability(ROA). While the variable CAR and LDR no significant effect on bank profitability. The value of adjusted R2 in regression models go public bank obtained at 0.869. This shows that the influence of independent variables namely CAR, NPL, LDR, NIM and BOPO to dependent variable (ROA) of 86.9% while the remaining 13.1% is influenced by other factors. On the results of partial hypothesis test (t test) on banks non go public indicates that the variable CAR and BOPO significant effect on bank profitability. While variable NPL, LDR and NIM no significant effect on bank profitability (ROA). The value of adjusted R2 in the regression model non go public bank earned 0.637. This shows that the influence of independent variables namely CAR, NPL, LDR, NIM and BOPO to dependent variable (ROA) of 63,7% while the remaining 36.3% is influenced by other factors.